Islamic culture and the question of women’s human rights in North Africa : a study of short stories by Assia Djebar and Alifa Rifaat - Soldati-Kahimbaara, Kulukazi (University of Pretoria, 2013)
Dissertation (MA (Pan African Literatures))--University of Pretoria, 2007.